PENGGUNAAN MYSQL DALAM PERANCANGAN DATABASE REKAM MEDIS ELEKTRONIK: STUDI LITERATUR - Anastasia Cyntia Dewi Kurniawati; Angel Septiana Uli (Smart Education, 2025)
Abstract: The amendment to the Minister of Health Regulation on medical records requires all healthcare facilities in Indonesia to implement Electronic Medical Records (EMR) no later than December 31, 2023. Many clinics, as part of these facilities, still rely on a file-based approach, resulting in scattered data that are difficult to retrieve, prone to duplication, and often inaccurate. This study aims to analyze the use of MySQL in designing a web-based EMR database. The method employed is a Systematic Literature Review (SLR), selecting articles based on inclusion and exclusion criteria, yielding 20 relevant journals. MySQL was chosen because it is an open-source database management system (DBMS) licensed under GPL, supports multi-user access, offers fast query performance, and provides adequate security features. Its advantages include easy distribution, compliance with standard SQL, and reliable performance for managing medical data. However, limitations such as inefficient decentralized configuration and longer execution times with large-scale data must be considered. The database design process follows five stages: Requirement, Design, Implementation, Verification, and Maintenance. The findings indicate that MySQL is suitable for EMR database design due to its functional strengths and flexibility, although large-scale optimization remains a challenge. Keywords: Electronic Medical Records, MySQL, Database Abstrak: Perubahan Peraturan Menteri Kesehatan tentang rekam medis mewajibkan seluruh fasilitas pelayanan kesehatan (fasyankes) di Indonesia menyelenggarakan Rekam Medis Elektronik (RME) paling lambat 31 Desember 2023. Klinik sebagai salah satu fasyankes masih banyak yang mengandalkan pendekatan file-based, sehingga data tersebar, sulit dicari, rawan duplikasi, dan sering tidak akurat. Penelitian ini bertujuan menganalisis pemanfaatan MySQL dalam perancangan database RME berbasis web. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan menyeleksi artikel sesuai kriteria inklusi dan eksklusi, dan diperoleh 20 jurnal relevan. MySQL dipilih karena merupakan sistem manajemen database (DBMS) open source berlisensi GPL, mendukung multiuser, memiliki kecepatan query yang baik, serta fitur keamanan yang memadai. Kelebihan MySQL meliputi kemudahan distribusi, dukungan standar SQL, dan performa yang andal untuk pengelolaan data medis. Namun, kelemahan seperti konfigurasi desentralisasi yang kurang efisien dan peningkatan waktu eksekusi pada data berskala besar perlu diperhatikan. Proses perancangan database mengikuti lima tahap: Requirement, Design, Implementation, Verification, dan Maintenance. Hasil kajian menunjukkan MySQL layak digunakan untuk perancangan database RME karena keunggulan fungsional dan fleksibilitasnya, meskipun optimalisasi skala besar tetap menjadi tantangan. Kata kunci: Rekam Medis Elektronik, MySQL, Database